Relation between superficial leg telangiectasias and deep venous insufficiency - Essam_E.M. Mohamed; Mahmoud A.E.-S. Makki; Tarek M.M. Mansour; Nesma H.F. El-Kareem (Al-Azhar Assiut Medical Journal)
Introduction Telangectasias and varicose veins have been linked to chronic venous valvular insufficiency causing great saphenous vein reflux. Duplex ultrasonography has become the practical standard for diagnosis, pretreatment mapping, peritreatment imaging, and patient follow-up of chronic venous valvular insufficiency. Patients and methods This is a prospective study that was carried out on patients presented with superficial leg telangiectasia, who attended outpatient clinic of the Dermatology and Andrology Department at Al Azhar University Hospital (Assiut) between October 2018 and June 2019. Results The study was carried on 80 patients with superficial leg telangiectasia, and their ages ranged from 17 to 66 years, with a mean of 43 years. At the end of the study, we found that, there is a significant relation between superficial leg telangiectasia and color Doppler findings, as ∼54% of our patients had abnormal deep venous system. Conclusion Factors such as positive family history of telangiectasia, long duration of telangiectasia, increased number of lesions, bilateral distribution of lesions, large diameter of lesions, and mixed color of lesions can predict deep venous system affection using color Doppler ultrasound in patients with superficial leg telangiectasia.